The Relationship between Smoking Behavior and Sleep Patterns in Young Adults (18–40 Years Old) - Sofiya Chairani; Idrawati Bahar; Yessi Fadriyanti (Journal of Applied Holistic Nursing Science, 2025)
Background: Sleep patterns reflect an individual’s ability to obtain the amount of sleep needed. One of the lifestyle factors that affects sleep patterns is smoking behavior. In modern society, young adults are particularly affected by smoking habits, with some smokers believing that smoking helps them relax and forget life’s problems, no matter how serious, and that smoking improves their mood. This study aimed to identify the relationship between smoking behavior and sleep patterns in young adults (18–40 years) in the Seberang Palinggam subdistrict. Methods: This was a correlational analytic study with a cross-sectional design. Data were collected from September 2023 to July 2024. The population consisted of 1,478 young adults aged 18–40 years in Seberang Palinggam, and 100 participants were selected using probability sampling techniques. Data were collected using a questionnaire and processed through editing, coding, entry, cleaning, and tabulating. Analysis was conducted using the Chi-square test (95% CI). Results: Statistical test results showed that most young adults engaged in heavy smoking behavior (52 respondents, 52.0%) and had poor sleep patterns (65 respondents, 65.0%). Based on bivariate analysis with the Chi-square test, the p-value was 0.027 (P < 0.05), indicating a significant relationship between smoking behavior and sleep patterns in young adults (18–40 years) in the Seberang Palinggam subdistrict. Conclusion: The study shows a significant relationship between smoking behavior and sleep patterns. Most young adult heavy smokers have poor sleep. Educational efforts and interventions are needed to reduce smoking habits and improve their sleep quality.